Improved formulations for higher order absorbing boundary conditions - Ramadan, O; Niazi, AY (Iee-Inst Elec Eng, 1997)
New formulations for higher order ABCs are introduced. Third and fourth order ABCs are reduced to first and second order derivatives with each one having one additional integral term. Considerable reductions in computer storage and computational time are achieved.
Keywords: electromagnetic waves; finite-difference time domain method